AN EMPIRICAL STUDY ON CUSTOMER BEHAVIOR TOWARDS ONLINE BANKING SERVICES IN UNA DISTRICT, HIMACHAL PRADESH - Ugyal, Neha (International Journal of Psychosocial Rehabilitation, 2020)
Different banks offer different services according to their customer’s demand and preference. In the current scenario, online banking services changes as the advance technologies introduced day by day and transform the face of traditional banking services. Now most of the banking services are available online or in electronic mode, which customers can use as per their convenience. The objective of this paper was to identify the preference of the customers regarding online banking services in Una region and to know the constraints faced by them while availing the same. The study was empirical in nature, for that total 250 respondents were selected from rural as well as from urban areas of Una based on random sampling technique, out of those 50 were not availing online banking services. So, only 200 valid responses were generated. Only commercials banks were considered for the study and data was collected through standardized questionnaire based on five -point likert scale. For analysis, the data descriptive statistics and factor analysis method were applied with the help of SPSS 23 version.